Shear strength of concrete block beams: Assessment of international codes and influence of shear span and longitudinal reinforcement - Pasquantonio, R. D.; Parsekian, G. A.; Soudais, P. R. N.; Camacho, J. S. [UNESP]; Modena, C.; DaPorto, F.; Valluzzi, M. R. (Crc Press-balkema, 2016)
Concrete block beam design must satisfy the Ultimate Limit State both for bending and shear loads. Among the factors that influence the shear load capacity of a concrete block beam, two are assessed in this paper: the apparent increase of shear strength as a function of the shear span [M-max/(V-max d)] and the ratio between longitudinal reinforcement and beam cross section. The first factor can be explained, among other things, because part of the load is transferred to the beam supports by compression strut and not completely by shear stresses. The second factor can be explained by rebar dowel action. Comparing international codes, several differences on these matters are observed. Brazilian code considers shear span and reinforcement ratio effects while North-American and Australian codes consider only one effect (shear span and reinforcement ratio, respectively). From an analysis of experimental data available in the literature, code formulations were assessed. Concerning the reinforcement ratio, large beams with transversal reinforcement are not much influenced by the effect. However, considering the reinforcement ratio may be interesting in the design of small lintels without shear reinforcement.